Emotional appeals in advertising banking services - Mogaji, Emmanuel (Emerald Publishing Limited, 2018)
Advertisements are considered as stimuli which consumers will respond to. Banks can develop emotionally appealing advertisements, but they are not guaranteed a positive emotional reaction. The unprecedented turbulence and uncertainty experienced in the banking industry has increased the need to appear more appealing to consumers. Taking into consideration the global financial crisis, the current challenges of competition and open banking, and the looming threat of Brexit, this book explores how UK banks are pulling at consumers heart strings with appeals that are often filtered through personal ideologies, life experiences and previous exposure to brands. It investigates consumers perception of this strategy, as well as the wider implications of using emotional appeals in financial services advertising.Based on empirical data and research, this books will prove invaluable to students, researchers and managers alike.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Advertising -- Banks and banking; Business & Economics -- Marketing -- General; Sales & marketing